Disclosing biological assets: A catalytic role in enhancing financial performance of agricultural companies - Almas, Maymurita Jihana; Widiyanti, Novi Wulandari; Wardhaningrum, Oktaviani Ari (Journal of Accounting and Investment, 2025)
Research aims: The study objectively investigates the connection between biological asset intensity and financial performance across businesses, focusing on the mediating role of biological asset disclosure.Design/Methodology/Approach: This study's research design is quantitative and explanatory. Agricultural company listings in the Indonesia Stock Exchange are those that were listed between 2021 and 2023. The sample was chosen using purposive sampling, which was predicated on predetermined criteria. Data were analyzed using Eviews 12 and mediation models were applied using linear regression analysis.Research findings: The findings demonstrate that financial performance is positively impacted by biological asset intensity. Additionally, biological asset intensity has a beneficial effect on biological asset disclosure, which raises the financial performance of the company. Additionally, disclosure of biological assets serves as a partial mediator in the association between financial performance and biological asset intensity. Theoretical contribution/Originality: By proving that this study contributes to the body of evidence showing that the association between biological asset intensity and financial success is mediated by biological asset transparency. Practitioner/Policy implication: Scholars are encouraged by the results to look into how biological assets and financial performance are related. Focusing on the significance of disclosure procedures, the study also provides firms with practical information to assess how biological asset intensity affects financial performance.Research limitation/Implication: Some organizations registered on the IDX have financial report data available, although there is a lack of information on aspects such as biological asset disclosure and biological asset intensity, which are the main limitations.